Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1186/s12864-022-08431-w
|View full text |Cite|
|
Sign up to set email alerts
|

Comparative transcriptome analysis reveals immunoregulation mechanism of lncRNA-mRNA in gill and skin of large yellow croaker (Larimichthys crocea) in response to Cryptocaryon irritans infection

Abstract: Background Cryptocaryonosis caused by Cryptocaryon irritans is one of the major diseases of large yellow croaker (Larimichthys crocea), which lead to massive economic losses annually to the aquaculture industry of L. crocea. Although there have been some studies on the pathogenesis for cryptocaryonosis, little is known about the innate defense mechanism of different immune organs of large yellow croaker. Results In order to analyze the roles of lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Among the 23 genes previous studies have shown their correlation with AD, we have: GFAP [ 41 , 42 ], PDGFRβ [ 43 45 ], NFKBIA [ 46 ], TNFRSF1B [ 47 ], NOTCH1 [ 48 ], BCL6 [ 49 ], CSF1R [ 50 ], LEP [ 51 ], DCLRE1C [ 52 ], KCNJ10 [ 53 ], MAP2K1 [ 54 ], VIP [ 55 ], SNCA [ 56 ], ENO2 [ 57 ], SST [ 58 ], UCHL1 [ 59 ], HPRT1 [ 60 ], STAT4 [ 61 ], CD14 [ 62 ], ITGB2 [ 63 ], SPP1 [ 64 ], STX1A [ 65 ], and SYP [ 66 ]. And these genes are involved in the regulation of molecules associated with the complement system, for instance, GFAP [ 67 ], PDGFRβ [ 68 ], NFKBIA [ 69 ], TNFRSF1B [ 70 ], NOTCH1 [ 71 ], BCL6 [ 72 ], CSF1R [ 73 ], LEP [ 74 ], DCLRE1C [ 75 ], KCNJ10 [ 76 ], MAP2K1 [ 77 ], VIP [ 78 ], SNCA [ 79 ], ENO2 [ 80 ], SST [ 81 ], UCHL1 [ 82 ], HPRT1 [ 83 ], STAT4 [ 84 ], CD14 [ 85 ], ITGB2 [ 86 ], SPP1 [ 87 ], STX1A [ 88 ], and SYP [ 89 ]. However, few studies have discussed their role in AD pathology by modulating the complement system, our study may be a new perspective for our future exploration of the relationship between AD and the complement system.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 23 genes previous studies have shown their correlation with AD, we have: GFAP [ 41 , 42 ], PDGFRβ [ 43 45 ], NFKBIA [ 46 ], TNFRSF1B [ 47 ], NOTCH1 [ 48 ], BCL6 [ 49 ], CSF1R [ 50 ], LEP [ 51 ], DCLRE1C [ 52 ], KCNJ10 [ 53 ], MAP2K1 [ 54 ], VIP [ 55 ], SNCA [ 56 ], ENO2 [ 57 ], SST [ 58 ], UCHL1 [ 59 ], HPRT1 [ 60 ], STAT4 [ 61 ], CD14 [ 62 ], ITGB2 [ 63 ], SPP1 [ 64 ], STX1A [ 65 ], and SYP [ 66 ]. And these genes are involved in the regulation of molecules associated with the complement system, for instance, GFAP [ 67 ], PDGFRβ [ 68 ], NFKBIA [ 69 ], TNFRSF1B [ 70 ], NOTCH1 [ 71 ], BCL6 [ 72 ], CSF1R [ 73 ], LEP [ 74 ], DCLRE1C [ 75 ], KCNJ10 [ 76 ], MAP2K1 [ 77 ], VIP [ 78 ], SNCA [ 79 ], ENO2 [ 80 ], SST [ 81 ], UCHL1 [ 82 ], HPRT1 [ 83 ], STAT4 [ 84 ], CD14 [ 85 ], ITGB2 [ 86 ], SPP1 [ 87 ], STX1A [ 88 ], and SYP [ 89 ]. However, few studies have discussed their role in AD pathology by modulating the complement system, our study may be a new perspective for our future exploration of the relationship between AD and the complement system.…”
Section: Discussionmentioning
confidence: 99%
“…Through long-period cultivation and trials, the arti cial breeding of L. crocea was overcame (Zhao et al, 2021). But with the increasing consumption and product need, germplasm was urged to be improved under the threat of diseases bursting frequently (Bai et al, 2022). Genomic editing technology had been applied to kinds of farm animals including pig, sheep, bream and carp to produce superior traits, which showed great prospect for optimizing genotypes of L. crocea.…”
Section: Current Problems Challenges and Future Perspectivesmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], it was reported that the authorship panel was missing an equal contribution designation for Yuilin Bai and Mei Wang. The original article [ 1 ] has been updated to include this.…”
mentioning
confidence: 99%